Integration of a contraception clinic into an opioid treatment setting to improve contraception knowledge, accessibility and uptake: a pilot study - Carolyn A. Day; Bethany White; Sharon E. Reid; Molly Fowler; Kirsten I. Black (Elsevier, 2020)
Abstract Objective: To assess the feasibility and acceptability of integrating a contraception clinic within an opioid agonist treatment (OAT) service to improve access to contraception, especially long‐acting reversible methods of contraception (LARC), for women receiving OAT, who have increased risk of unplanned pregnancies and adverse pregnancy outcomes. Methods: A contraception clinic was established at a Sydney OAT service. Forty‐eight female OAT clients were surveyed regarding their contraception knowledge and needs. Interested and eligible women were referred to the contraception clinic. Results: Women were aged a median of 39 years (range 24-54 years). Most women (83%) agreed it was acceptable for their OAT clinician to discuss contraception with them. Eight women reported current LARC use and 21 reported they would consider using LARC. Twenty‐three women were eligible for contraception (sexually active, aged <50 years, not using contraception, wishing to avoid pregnancy). Six months post‐survey two women had presented to the clinic and two reported an unintended pregnancy. Conclusion: Uptake of an on‐site contraception service within OAT clinic was low, despite participants' expressed willingness to use the service. Access is therefore not the only driver of low contraception uptake for this group. Implications for public health: Other issues besides access to contraception warrant investigation to improve contraception uptake for women receiving OAT.